SOCIODEMOGRAPHIC AND MATERNAL BEHAVIOR ANALYSIS RELATED TO THE INCIDENCE OF STUNTING AMONG TODDLERS IN THE WORKING AREA OF UPT PUSKESMAS RAPPANG SIDENRENG RAPPANG REGENCY - Hesti Hayati; Devy Febrianti; Zulkarnain Sulaiman; Pratiwi Ramlan (CV. Fahr Publishing, 2026)
Stunting is a global public health issue that affects physical growth, mental development, and the quality of human resources. In Indonesia, the prevalence of stunting decreased from 30.8% in 2018 to 19.8% in 2024, yet it remains an important concern. This study aimed to analyze the relationship between sociodemographic characteristics and maternal behavior with the incidence of stunting among children under five in the working area of UPT Puskesmas Rappang, Sidenreng Rappang Regency. This study used a quantitative method with a cross-sectional design involving 96 mothers of toddlers selected through purposive sampling. Data were collected using structured questionnaires and analyzed using the chi-square test with SPSS software. The results showed that maternal knowledge (p=0.018), family economic status (p=0.030), early initiation of breastfeeding (EIBF) (p=0.001), and parenting patterns (p=0.001) had significant relationships with stunting among children under five. Respondents with better knowledge, higher family economic status, supportive EIBF practices, and good parenting patterns tended to have a higher proportion of non-stunted children. Parenting patterns and EIBF showed stronger associations compared to other variables. It can be concluded that maternal knowledge, family economic status, early initiation of breastfeeding, and parenting patterns are significantly associated with stunting among children under five.